(untitled) (ItalianoLinguadue, 2016)
Il presente contributo si propone di fornire una descrizione della struttura del Vocabolario Patronimico di Francesco Cherubini e delle fonti empiriche consultate per la sua compilazione. Si accennerà poi a due questioni ricorrenti nel dibattito sulla formazione degli etnici in italiano, ovvero, la presenza di varianti allomorfiche o suppletive, e la motivazione morfo-pragmatica sottesa all’impiego di alcuni suffissi derivativi nella formazione di etnici e aggettivi deonomastici, cercando di chiarire quale attenzione tali tematiche abbiano ricevuto nella riflessione linguistica di Francesco Cherubini. Si formuleranno infine alcune osservazioni conclusive, evidenziando luci ed ombre del Vocabolario Patronimico e sottolineando alcuni degli spunti che tale opera ancora può offrire agli studiosi contemporanei. The formation of ethnic words in Francesco Cherubini’s reflection on language The aim of this paper is to describe the structure and contents of Francesco Cherubini’s Vocabolario Patronimico, as well as the empirical sources consulted for its compilation. We will address two of the most common issues in the debate on the formation of ethnic nouns and adjectives in Italian, namely the existence of allomorphs and supplementary variants, and the morpho-pragmatic motivation displayed by some of the derivative suffixes occurring in ethnic nouns and adjectives derived from both personal and place names. We will offer a few observations on the place occupied by the above-mentioned issues in Cherubini’s thought and, by analyzing the strengths and weaknesses of the Vocabolario Patronimico, we will draw attention to a few topics which may be of some interest to contemporary scholars.